1993
DOI: 10.1128/cmr.6.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility testing

Abstract: Unlike antibacterial susceptibility testing, reliable antifungal susceptibility testing is still largely in its infancy. Many methods have been described, but they produce widely discrepant results unless such factors as pH, inoculum size, medium formulation, incubation time, and incubation temperature are carefully controlled. Even when laboratories agree upon a common method, interlaboratory agreement may be poor. As a result of numerous collaborative projects carried out both independently and under the aeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
198
1
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(214 citation statements)
references
References 128 publications
11
198
1
4
Order By: Relevance
“…The lid was left ajar for 40 min to allow the acetone to evaporate. Preliminary tests showed that a 40 min drying time was optimal for minimizing variation ( Variation in fungal growth rates among assays was minimized by using a stock spore suspension (Rex et al 1993). The stock suspension was made with spores of Aspergillus sydowii isolated from San Salvador, Bahamas (Smith et al 1996) and filtered through gauze to remove hyphal mats and then suspended in de-ionized water at a concentration of 2 150 000 spores ml -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The lid was left ajar for 40 min to allow the acetone to evaporate. Preliminary tests showed that a 40 min drying time was optimal for minimizing variation ( Variation in fungal growth rates among assays was minimized by using a stock spore suspension (Rex et al 1993). The stock suspension was made with spores of Aspergillus sydowii isolated from San Salvador, Bahamas (Smith et al 1996) and filtered through gauze to remove hyphal mats and then suspended in de-ionized water at a concentration of 2 150 000 spores ml -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The test method can affect the level of antifungal activity determined (Rex et al, 1993(Rex et al, , 1995. The NCCLS recommend the use of RPMI 1640 buffered to pH 7 .…”
Section: Effect Of Test Methods On In Vitro Activity Of Dihydropyrrolementioning
confidence: 99%
“…Despite great advances in the standardization of antifungal susceptibility testing, azole endpoint determination continues to be problematic and subjective and a major source of interlaboratory variability (6,18,23). The trailing-growth phenomenon is often responsible for these difficulties, whereby partial inhibition of fungal growth occurs over the range of azole concentrations (6,13,14,23).…”
mentioning
confidence: 99%
“…The trailing-growth phenomenon is often responsible for these difficulties, whereby partial inhibition of fungal growth occurs over the range of azole concentrations (6,13,14,23).…”
mentioning
confidence: 99%